2014
DOI: 10.1007/s10661-014-3866-7
|View full text |Cite
|
Sign up to set email alerts
|

Methods, fluxes and sources of gas phase alkyl nitrates in the coastal air

Abstract: The daily and seasonal atmospheric concentrations, deposition fluxes and emission sources of a few C3-C9 gaseous alkyl nitrates (ANs) at the Belgian coast (De Haan) on the Southern North Sea were determined. An adapted sampler design for low- and high-volume air-sampling, optimized sample extraction and clean-up, as well as identification and quantification of ANs in air samples by means of gas chromatography mass spectrometry, are reported. The total concentrations of ANs ranged from 0.03 to 85 pptv and consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Similar to O 3 , observed RONO 2 usually showed a peak at midday, reflecting the dominance of photochemical reactions. , Besides, studies have confirmed that RONO 2 are also directly emitted from the oceans, particularly for light (<C 2 ) RONO 2 . , Biomass burning is also a source of RONO 2 , which are quickly formed through the pathway of RO + NO 2 . , The source contributions may vary in different locations and/or under the influence of different origins of air masses. , …”
Section: Introductionmentioning
confidence: 88%
“…Similar to O 3 , observed RONO 2 usually showed a peak at midday, reflecting the dominance of photochemical reactions. , Besides, studies have confirmed that RONO 2 are also directly emitted from the oceans, particularly for light (<C 2 ) RONO 2 . , Biomass burning is also a source of RONO 2 , which are quickly formed through the pathway of RO + NO 2 . , The source contributions may vary in different locations and/or under the influence of different origins of air masses. , …”
Section: Introductionmentioning
confidence: 88%